Polymorphisms of the serotonin transporter and receptor genes: susceptibility to substance abuse - Herman AI; Balogh KN (Dove Medical Press, 2012)
Aryeh I Herman, Kornelia N BaloghDepartment of Psychiatry, VA Connecticut Healthcare/Yale University School of Medicine, West Haven, CT, USAAbstract: Serotonin (5-hydroxytryptamine [5-HT]) is an important neurotransmitter implicated in regulating substance-use disorder (SUD) acquisition, maintenance, and recovery. During the past several years, an abundance of research has begun discovering and describing specific 5-HT genetic polymorphisms associated with SUDs. Genetic variations in the 5-HT system, such as SLC6A4, HTR1B, HTR2A, HTR2C, HTR3 (HTR3A, HTR3B, HTR3C, HTR3D, and HTR3E), likely play a role contributing to SUD patient heterogeneity. The 5-HT transporter-linked polymorphic region S allele, located in SLC6A4, has now been modestly associated with alcohol dependence in two large meta-analyses. Additional 5-HT genes may also play a role but have not been extensively investigated. A limited number of SUD treatment studies have included 5-HT gene variation as moderating treatment outcomes, but the results have been equivocal. Future research on 5-HT addiction genetics should adopt whole-genome sequencing technology, utilize large study samples, and collect data from multiple ethnic groups. Together, these methods will build on the work already conducted with the aim of utilizing 5-HT genetics in SUD treatment settings.Keywords: serotonin, genetic, substance dependence, addiction, alcohol, drug